Strategies and performance of the CMS silicon tracker alignment during LHC Run 2 - Adam, Wolfgang; Andrejkovic, Janik Walter; Bergauer, T.; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Nuclear instruments and methods in physics research. Section A: accelerators, spectrometers, detectors and associated equipment)
The strategies for and the performance of the CMS silicon tracking system alignment during the 2015-2018 data-taking period of the LHC are described. The alignment procedures during and after data taking are explained. Alignment scenarios are also derived for use in the simulation of the detector response. Systematic effects, related to intrinsic symmetries of the alignment task or to external constraints, are discussed and illustrated for different scenarios.